2015
DOI: 10.1016/j.soard.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Nonnormative eating behavior and psychopathology in prebariatric patients with binge-eating disorder and night eating syndrome

Abstract: BED and NES were shown to be prevalent among prebariatric patients, with some degree of overlap between diagnoses. Associations with nonnormative eating behavior and psychopathology point to their clinical significance and discriminant validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 25 publications
5
47
1
4
Order By: Relevance
“…Other current findings contradict the assumption that the patients might have under‐report psychopathology. In accordance with our hypothesis, the prevalence of probable eating, anxiety, and major depressive disorders in the present sample was as high as expected based on literature (Baldofski et al, ; Brunault et al, ; Brunault et al, ; Ivezaj et al, ; Koball et al, ; Meule et al, ; Meule et al, ; Miller‐Matero et al, ; Ouellette et al, ). The current results further resemble findings from previous studies in bariatric surgery patients that indicate that those with FA are more likely than those without FA to exhibit eating disorder and anxiety and depressive disorder symptoms (Brunault et al, ; Koball et al, ; Meule et al, ; Miller‐Matero et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Other current findings contradict the assumption that the patients might have under‐report psychopathology. In accordance with our hypothesis, the prevalence of probable eating, anxiety, and major depressive disorders in the present sample was as high as expected based on literature (Baldofski et al, ; Brunault et al, ; Brunault et al, ; Ivezaj et al, ; Koball et al, ; Meule et al, ; Meule et al, ; Miller‐Matero et al, ; Ouellette et al, ). The current results further resemble findings from previous studies in bariatric surgery patients that indicate that those with FA are more likely than those without FA to exhibit eating disorder and anxiety and depressive disorder symptoms (Brunault et al, ; Koball et al, ; Meule et al, ; Miller‐Matero et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…There is no difference between BED and NES patients on subjective binge eating episodes and other disordered eating like emotional eating and food addiction. 4,5 All eating disorders prevalence rates in our study were lower than we predicted. Also there was no significant relationship between having any kind of eating disorder and sociodemografic variables, comorbid medical conditions (Table 3).…”
Section: Discussioncontrasting
confidence: 73%
“…Baldofski et al, reported that 8.2% of their bariatic sample had NES diagnosis and 4.3% had BED diagnosis and 3.9% of the sample had both. 4 6.5% of our sample had both BED and NES diagnosis. In our study, the prevalence rate of overlap was higher than Baldofski et al's (6.5% vs. 3.9%).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations